The Aboriginal Version: Erna Brodber’s "One Bubby Susan" - Adams, Michelene (International Journal of Bahamian Studies, 2008)
In the story "One Bubby Susan" (1990), by Jamaican sociologist and author, Erna Brodber, the narrator attempts to persuade the listener that a petroglyph in a cave in Jamaica that has been identified in texts as the depiction of an Arawak female is, in fact, not a work of art, but the outline of an actual woman’s body. The outline was left in the rock when she was stoned to death by her own people. The contemporary Jamaican narrator recounts the tale which she has been told by the ghost of the Arawak female herself, and, by telling her life across centuries to the narrator, Susan challenges her own marginalization as Aboriginal and as woman. In the paper I briefly consider how the Aboriginal has remained on the margins in colonial and even in more modern Caribbean discourse. I examine how Brodber recasts the Aboriginal in the central role. First, I consider how she questions the authority of official Histories and scribal culture generally. Then, I explore how the Arawak is re-vivified through the metaphors of the body and the voice. Of course, the issues of history, corporeality and voice are all crucial in feminist discourse, so I also explore what Brodber is suggesting with regard to gender while re-presenting the Aboriginal.